Homozygosity for a Novel Missense Mutation in the Prothrombin Gene Causing a Severe Bleeding Disorder - Poort, S R; Michiels, J J; Reitsma, P H; Bertina, R M (Thrombosis and Haemostasis, 1994)
A patient with a severe bleeding tendency and hypoprothrombin-emia (Factor II activity 2%, Factor II antigen 5%) was screened for the presence of alterations in his prothrombin gene. Direct sequencing of PCR fragments derived from the coding and flanking regions of the prothrombin gene, revealed that the patient was homozygous for an A ⟶ G substitution in exon 3. This substitution predicts the replacement of Tyr 44 (TAC) by Cys (TGC) in the prothrombin molecule. Both parents were found to be heterozygous for the same mutation. Further family studies revealed complete cosegregation of the mutation with the prothrombin deficiency. Only the five homozygous brothers and sisters of the propositus were clinically affected (severe hemorrhages including epistaxis, soft tissue, muscle and joint bleedings in all, and severe hemorrhages in the two women). The bleeding tendency therefore seems to inherit as an autosomal recessive trait.